2020
DOI: 10.1016/j.jnutbio.2019.108263
|View full text |Cite
|
Sign up to set email alerts
|

Stigmasterol stimulates transintestinal cholesterol excretion independent of liver X receptor activation in the small intestine

Abstract: Despite advances in healthcare, cardiovascular disease (CVD) remains the leading cause of death in the United States. Elevated levels of plasma cholesterol are highly predictive of CVD and stroke and are the principal driver of atherosclerosis. Unfortunately, current cholesterol lowering agents, such as statins, are not known to reverse atherosclerotic disease once it has been established. In preclinical models, agonists of nuclear receptor, LXR, have been shown to reduce and reverse atherosclerosis. Phytoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…These findings indicated that Que could protect against liver injury induced by CCl 4 . Que also reduced the levels of expression of NF-κB p65 and p-IκBα elevated in response to CCl 4 treatment, indicating that the Que in AR could exert liver-protecting effects by regulating the NF-κB pathway signaling [ 33 35 ]. Moreover, experimental validation showed that the liver-protecting effect of the active ingredients of AR was closely related to the suppression of inflammation, further confirming the reliability of the results of systematic network pharmacological screening, as well as the prediction of the molecular mechanism in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicated that Que could protect against liver injury induced by CCl 4 . Que also reduced the levels of expression of NF-κB p65 and p-IκBα elevated in response to CCl 4 treatment, indicating that the Que in AR could exert liver-protecting effects by regulating the NF-κB pathway signaling [ 33 35 ]. Moreover, experimental validation showed that the liver-protecting effect of the active ingredients of AR was closely related to the suppression of inflammation, further confirming the reliability of the results of systematic network pharmacological screening, as well as the prediction of the molecular mechanism in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies have shown both an increase [ 28 , 29 , 168 , 169 ] and a decrease [ 167 , 170 ] in the m-RCT process or RCT molecular players following high-cholesterol dietary (from 0.2% to 2% w/w ) exposure. On the other hand, the enrichment of diets with phytosterols (0.3–2% w/w ) has generated more consistent results, highlighting effects such as reduced intestinal absorption and increased fecal elimination of cholesterol [ 171 , 172 , 181 , 182 ].…”
Section: Effects Of Sterols On Rct In Animal Modelsmentioning
confidence: 99%
“…Ferruginol merupakan senyawa golongan diterpenoid yang telah dilaporkan memiliki khasiat antivirus (Roa-Linares et al 2016), antimalaria (González et al 2014), antimikroba dan antioksidan (Mothana et al 2019). Stigmasterol dan γ-sitosterol merupakan senyawa fitosterol yang telah dilaporkan berkhasiat sebagai antidiabetes (Balamurugan et al 2011), imunosupresi (Antwi et al 2017;Le et al 2017), dan membantu sekresi kolesterol (Lifsey et al 2020). Berdasarkan kandungan metabolit dan potensi khasiat menunjukkan bahwa tanaman torbangun selain bermanfaat untuk stimulus produksi ASI juga dapat dikonsumsi sebagai obat herbal dengan khasiat potensi yang cukup beragam.…”
Section: Pembahasanunclassified